Pelatihan Pembuatan Biochar dari Limbah Sekam Padi Menggunakan Metode Retort Kiln - Maria Maghdalena Diana Widiastuti; Bonny Lantang (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Utilization of rice husk waste into biochar could become one of the innovations that can be applied for farmers to overcome the reducing acidity of soil, increasing crop productivity, and savings carbon stocks to address global environmental issues. The purpose of this training are: 1) To introduce benefits of biochar as a soil improvement for farmer groups in Kampung Jaya Makmur; 2) To practice biochar production using retort kiln method from rise husk; 3) To apply biochar in as infertile or acid soil; 4) Establish a business group biochar production; and (5) To assist biochar business groups during the production, processing and marketing process. This training uses PLA (Participatory Learning and Action) by empowering pioneer farmers who had been trained in biochar production. The participants of this training are two farmer groups, owner of rice mills, and village officials Jaya Makmur, Kurik Subdistrict, Merauke District. The result of this training are 40 farmers know about the importance of biochar for their agricultural land as soil improvement reduce the acidity of soil. Participants also know how to produce biochar using retort kilns, and conventional methods and the disadvantages and advantages of each method, some farmers are able to make their own biochar by conventional methods. There are two farmers want apply biochar in their land in next planting season and establish a biochar production group. Conclusion of this training are the community knows about the importance of biochar and methods of efficient production and reduce pollution by using retort kiln.